2013
DOI: 10.2174/15701638113109990034
|View full text |Cite
|
Sign up to set email alerts
|

Effects of N-Acetyl-L-Cysteine and Hyaluronic Acid on HBOC-201- Induced Systemic and Cerebral Vasoconstriction in the Rat

Abstract: Hemoglobin-based oxygen carrier-201 (HBOC) was developed as a resuscitative fluid but concerns exist over potentially adverse vasoconstriction. This study evaluated whether concurrent IV (intra venous) N-acetyl-L-cysteine (NAC) or hyaluronic acid (HA) would attenuate HBOC-associated vasoconstriction, assessed by systemic blood pressures and cerebral pial microvasculature, when administered to healthy, anesthetized rats. Rats (8-9/group) received a 30 min infusion of 3 ml/kg HBOC, HBOC plus 600 mg/kg NAC (HBOC/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 0 publications
4
16
0
Order By: Relevance
“…but this change occurred equally in both test and control groups. This vasoconstriction was similar to results from another study in salinetreated rats (Abutarboush et al, 2013) and suggests the effects may be related to surgical preparation of the model, anesthesia, intra-cranial pressure changes, or surface temperature changes in the exposed brain. Nonetheless, vasoconstriction after topical BaCl 2 application at the end of the study confirmed the responsiveness and viability of the vessels.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…but this change occurred equally in both test and control groups. This vasoconstriction was similar to results from another study in salinetreated rats (Abutarboush et al, 2013) and suggests the effects may be related to surgical preparation of the model, anesthesia, intra-cranial pressure changes, or surface temperature changes in the exposed brain. Nonetheless, vasoconstriction after topical BaCl 2 application at the end of the study confirmed the responsiveness and viability of the vessels.…”
Section: Discussionsupporting
confidence: 86%
“…Pial arteriolar diameters were measured at the same locus throughout the experiment using the computer program CellSens (Olympus, 2010). Similar to previous cerebrovascular studies (Abutarboush et al, 2013;Rebel et al, 2006;Rebel et al, 2003), the pial arteriolar vessel diameters were divided into three categories based on size at baseline measurement: (1) "small" vessels having a diameter b 50 μm, (2) "medium" vessels with diameters of 50 to 100 μm, and (3) "large" vessels with diameters N 100 μm. The division into size categories was based on the fact that the amount of smooth muscle increases with vessel size which could lead to differences in degree of vessel contraction (Rosenblum, 1976).…”
Section: Study 1 Healthy Ratsmentioning
confidence: 99%
“…HR was significantly different among the groups at baseline (T0) but was still within the normal range for rats under the anesthesia regimen used in this study [13,14,15,16,17] and did not exhibit any cumulative change (comparing T0 to T150) over time within any of the groups (Table 1). The only significant change in HR after an individual infusion was a slight transient increase in the 0.9% NaCl group after the third infusion.…”
Section: Resultsmentioning
confidence: 72%
“…18,19 A stereomicroscope (SZ16, Olympus, Japan) equipped with a DP-73 digital camera was used for direct visualization and imaging of pial vessels at 80X. Arteriole sizes were divided into three categories for analysis of microvessel measurements: small (<50 µ m), medium (50-100 µ m), and large-sized (>100 µ m) vessels.…”
Section: Pial Arteriolar Vessel Diameter Study (Experiments 1)mentioning
confidence: 99%
“…Grouping the vessels into these categories is the convention in the microvascular literature 19,23 and is scientifically justified since the amount of smooth muscle increases with vessel size and the degree of contraction correlates with the amount of vascular smooth muscle. 24 6…”
Section: Pial Arteriolar Vessel Diameter Study (Experiments 1)mentioning
confidence: 99%